2020
DOI: 10.1007/s40122-020-00189-x
|View full text |Cite|
|
Sign up to set email alerts
|

Gabapentinoid Benefit and Risk Stratification: Mechanisms Over Myth

Abstract: Introduction: Recent years have seen a dramatic escalation of off-label prescribing for gabapentin and pregabalin (gabapentinoids) owing in part to generic versions of each being released over the past two decades, but also in part as a response to increasing calls for multimodal and non-opioid pain management strategies. In this context, several recent articles have been published alleging widespread misuse, with speculations on the unappreciated addictive potential of the gabapentinoid class of Digital Featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
49
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 59 publications
(78 reference statements)
1
49
0
3
Order By: Relevance
“…The authors also describe that the benefits of gabapentinoid therapy far outweigh the risks [1]. While we concur this is true for many patients, it may not be the case for all.…”
supporting
confidence: 50%
See 3 more Smart Citations
“…The authors also describe that the benefits of gabapentinoid therapy far outweigh the risks [1]. While we concur this is true for many patients, it may not be the case for all.…”
supporting
confidence: 50%
“…Blinded studies have identified that gabapentinoids produce similar drug-liking effects to diazepam [7] and tetrahydrocannabinol (the psychoactive component of cannabis) [8] in patients with a history of substance use disorder. The authors also state that studies indicate that the ''vast majority of misuse events appear to occur in an attempt to ameliorate opioid withdrawal symptoms'' [1], which is simply not borne out in the current literature. Several studies have assessed motivators for gabapentinoid use.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…We would like to thank Peckham et al [1] for their critique of our review [2] outlining the benefits and risks of gabapentinoids (GPNs) in the context of general medical, specialty pain management, and addiction medicine practice. Our targeted narrative review of this subject is intended to present a balanced perspective of salient issues to, and ameliorate current confusion regarding the class of drugs among clinicians, pharmacists, and public health workers alike.…”
Section: Gabapentinoids: Panacea or Pandora's Box?mentioning
confidence: 99%